Developing STEM Based Student’s Book for Grade XII Biotechnology Topics - Bevo Wahono; Aini Meitanti Rosalina; Anjar Putro Utomo; Erlia Narulita (Journal of Education and Learning (EduLearn), 2018)
The study aims to develop a valid, practical and effective Biology student’s book based on Science Technology Engineering and Mathematics (STEM) on the topic of biotechnology for Grade XII. The method applied for the study was research and development with the 4-D model. The subjects were 58 Grade XII students of SMAN 1 Muncar, Banyuwangi-Indonesia. The results showed that the average of validation result of STEM-based student’s book was 86.4% which fell under a strong valid category. The average percentage of legibility test and practicality were in very good category of 87.18% and 96.53%, respectively. Meanwhile, the average of effectiveness test was 0.77 of normalized gain categorized in high criteria. In conclusion, it could be determined that STEM-based student’s book of biotechnology is valid, pratical, and effectively used in learning process.